Treatment of Recalcitrant Mycotic Keratouveitis with Targeted Voriconazole Injection Combined with Hypopyon Drainage - Prateek Jain; Poulami Pal; Anshuman Pattnaik (Delhi Journal of Ophthalmology)
Fungal keratitis is a common yet obstinate condition to treat with a wide range of ocular morbidity. Factors such as compromised immunity of the patient, reduced drug penetration, refractory nature of the disease contribute to difficulty in treatment. A 65 year old chronic smoker was referred to us with left eye deep fungal keratitis with hypopyon which was not responding to topical treatment. The patient was diagnosed as Recalcitrant Mycotic Keratouveitis and was posted for targeted management including hypopyon drainage with Intrastromal and Intracameral Voriconazole injection; following which the condition improved significantly.